CLINICAL CHARACTERISTIC OF AFFECTIVE VIOLATIONS IN DISORDERS OF ADAPTATION FROM COMBATANTS - Ratsyborynska-Polyakova, N.V.; Rymsha, S.V. (World of Medicine and Biology, 2020)
A comprehensive clinicopsychopathological and pathopsychological study of 186 combatants with diagnosed stress reactions and adaptation disorders, who underwent inpatient treatment in the clinical departments of the Vinnitsa Regional Clinical Hospital of War Veterans was performed. The study included socio-demographic (questionnaire), clinical-anamnestic, clinical-psychopathological (clinical interview), psychodiagnostic (pathopsychological) and statistical methods. In the course of this study, the severity of affective disorders in the study group was established, data variability was determined, and a statistical-mathematical analysis of the survey results was carried out. The results of the proposed algorithm of psychodiagnostic research reflect the structure of changes in the affective sphere and certain personal predispositions in patients with affective variants of adaptation disorders. It was revealed that a cognitive defect can be formed later through the consolidation and progression of organic changes, and the transition of an adaptation disorder to a behavioral level will be associated with personality traits and characteristics of respondents’ social rehabilitation. Determination of clinical and psychopathological features of prevailing variants of adaptation disorders in combatants is the basis for the development of new diagnostic algorithms and integrated approaches to the treatment of this contingent.